Analysis of User Experience (UX) and User Interface (UI) on Digital Banking Applications to Increase Customer Satisfaction in Banten Province - Nafiz Annas; Rezty Arizta Putri; Deti Kurniati; Reni, Reni; Gurruh Dwi Septano (Universitas Muhammadiyah Palu, 2025)
Digital transformation in the banking sector has brought convenience to financial transactions through mobile banking applications. However, the quality of User Experience (UX) and User Interface (UI) is still a challenge, especially for people with low digital literacy. This service activity aims to improve the understanding and skills of the community in Banten Province in using digital banking applications effectively and safely. The implementation method includes an initial survey, simulation-based training, focus group discussions (FGDs), pre-post test evaluations, and the formation of village digital communities. The participants consisted of MSME players, housewives, and students, with a total of 120 people. The results of the activity showed a significant improvement in the digital literacy aspect, where the participants' understanding score rose from 52.3% to 83.7%. As many as 88% of participants were able to complete digital transactions independently after the training. The focus on digital security also increased user trust in the app. FGD findings indicated the need for improvement in application design, particularly interface navigation, icon size, and language simplification. Community-based UX/UI recommendations have been compiled and submitted to partner banks. The outputs of the activity include scientific articles, service reports, and the formation of a digital community forum for banking application users. This activity proves that an educative and participatory approach is able to answer the challenges of banking digitalization in real terms. This program is expected to become a replication model in an effort to increase digital financial inclusion based on local needs.